Dampak Modal dan Tenaga Kerja Terhadap Pendapatan Usahatani Jamur Tiram: Studi Kasus di Desa Laut Dendang - Sihombing, Humisar; Dina Sarah Syahreza; Hendra Saputra; Hesti Sabrina (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research was conducted in Desa Laut Dendang, Kecamatan Percut Sei Tuan. The population for this study consists of all oyster mushroom farms, totaling 150 individuals, with a sample size of 60 individuals selected using Random Sampling. The data collection instrument was a multiple-choice questionnaire that had been tested for validity and reliability. Classical assumption tests included tests for normality, multicollinearity, and heteroscedasticity. Hypothesis testing was conducted using multiple linear regression analysis, F-test, and t-test. The validity test results showed that rhitung > rtabel for each questionnaire item, and the reliability test yielded Cronbach's alpha values of 0.842 for variable X1, 0.725 for variable X2, and 0.680 for variable Y. These values are greater than the significant level of rtabel, which is 0.361. Data analysis for each variable produced the multiple regression equation Y = 8.839 + 0.344X1 + 0.227X2 + e. The R2 value of 0.544 indicates that X1 and X2 explain 54.4% of the variance in variable Y, while the remaining 45.6% is explained by other variables not included in this study. The partial test results indicate that each independent variable significantly affects the dependent variable, with a significance level less than 0.05. The simultaneous test results show an F-value of 6.812 with an Ftabel of 3.160, meaning Fhitung > Ftabel at a significance level (α) of 0.012 < 0.05. This means the hypothesis is accepted, indicating that Capital and Labor significantly affect the Income of Oyster Mushroom Farming in Desa Laut Dendang, Kecamatan Percut Sei Tuan.